Comparative Policy Agendas Theory, Tools, Data - Baumgartner, Frank R.; Breunig, Christian; Grossman, Emiliano (Oxford University Press, 2019)
The Comparative Agendas Project (CAP) brings together data on government activities in over twenty countries, and provides a consistent categorizing system to understand when a given institution of government in a particular country took action on any issue of public policy. All topics are covered, comprehensively, over several decades, in some countries going back to World War II. Because of the open-data philosophy that animates the international network of scholars involved in the project and their meticulous attention to comparability and common data coding conventions, the databases of the CAP represent an unprecedented resource for the study of public policy across national borders. In this major new book, leaders of each national team provide the background and information needed for anyone to understand how best to make use of these newly available historical databases. Interested users will range from novice students of public policy to accomplished scholars, from interested citizens to professional journalists, political or partisan activists, and professional staff of legislative assemblies or national administrative agencies. The book's sections include chapters introducing the CAP to a new audience, describing each national project, illustrating various cross-national uses and analyses that the CAP data allow, and concluding with ideas for further practical and research uses.